2000
DOI: 10.1021/ac000427o
|View full text |Cite
|
Sign up to set email alerts
|

A Planar pCO2 Sensor with Enhanced Electrochemical Properties

Abstract: To develop planar microchemical pCO2 sensing devices with improved electrochemical properties, we combined two advanced technologies. One is a differential sensor arrangement to simplify the microfabrication procedure by employing pH-sensitive gas-permeable membranes, and the other is the use of an enzyme (carbonic anhydrase) to shorten total measurement time by accelerating the rate of CO2 hydration. The adhesion of the polyurethane-matrix gas-permeable membrane is enhanced significantly by incorporating a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Originally, an ordinary glass electrode was used which is, however, not suitable for miniaturization. Therefore alternative pH measurement methods have been explored such as metal oxide electrodes (Tierney and Kim, 1993;Suzuki and Arakawa, 1999;Beyenal et al, 2004), solvent polymeric membrane electrodes (Opdycke and Meyerhoff, 1986;Shin et al, 2002;Zhao and Cai, 1997) and ion-selective field effect transistors (Arquint et al, 1993;Tsukada et al, 1990;Sekiguchi et al, 1998). Unfortunately, the above mentioned methods make use of an Ag/AgCl reference electrode which is known to suffer from drift and moreover needs regular maintenance because it is liquid filled.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, an ordinary glass electrode was used which is, however, not suitable for miniaturization. Therefore alternative pH measurement methods have been explored such as metal oxide electrodes (Tierney and Kim, 1993;Suzuki and Arakawa, 1999;Beyenal et al, 2004), solvent polymeric membrane electrodes (Opdycke and Meyerhoff, 1986;Shin et al, 2002;Zhao and Cai, 1997) and ion-selective field effect transistors (Arquint et al, 1993;Tsukada et al, 1990;Sekiguchi et al, 1998). Unfortunately, the above mentioned methods make use of an Ag/AgCl reference electrode which is known to suffer from drift and moreover needs regular maintenance because it is liquid filled.…”
Section: Introductionmentioning
confidence: 99%
“…Another planar potentiometric CO 2 sensor was described by Shin et al [38]. They developed a microchemical pCO 2 sensor based on both pH-sensitive and CO 2 -permeable membranes sensing in a differential arrangement.…”
Section: Trends In Electrochemical Co 2 Sensingmentioning
confidence: 99%
“…12 Planar differential CO 2 sensor based on buffered and unbuffered pH membrane electrodes. Adapted from [38] with permission Fig. 13 Scheme of an ISFET blood gas sensor described by Ekwinska et al Adapted from [39] with permission Trends in Electrochemical Sensing of Blood Gases which can be measured in terms of an amperometric signal.…”
Section: Trends In Electrochemical Co 2 Sensingmentioning
confidence: 99%
“…In addition, around 0.25 million people die each year prematurely due to improper management and lack of personal asthma monitoring tool. As well Kaitlin and Krull suggested that young adults (age [18][19][20][21][22][23][24][25] suffering from asthma should have a personal asthma monitoring device to assess their disease and decrease their risk of exacerbation and hospital admission [4]. Hence the early diagnosis of asthma and achieving acceptable asthma supervision at the right time remains evasive despite the existing methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies were offline. Furthermore, the existing capnograph is bulky, costly and cannot estimate components of physiological dead space as well as not able to distinguish the end of expiration from the beginning of inspiration [24][25]. Thus, we have developed a light weight, effort independent and portable asthma monitoring device that can measure the expired CO 2 concentrations and differentiate early stage of asthma.…”
Section: Introductionmentioning
confidence: 99%